Algebra Examples

Solve for j 3(5j+2)=2(3j-6)
3(5j+2)=2(3j-6)
Step 1
Simplify 3(5j+2).
Tap for more steps...
Step 1.1
Rewrite.
0+0+3(5j+2)=2(3j-6)
Step 1.2
Simplify by adding zeros.
3(5j+2)=2(3j-6)
Step 1.3
Apply the distributive property.
3(5j)+32=2(3j-6)
Step 1.4
Multiply.
Tap for more steps...
Step 1.4.1
Multiply 5 by 3.
15j+32=2(3j-6)
Step 1.4.2
Multiply 3 by 2.
15j+6=2(3j-6)
15j+6=2(3j-6)
15j+6=2(3j-6)
Step 2
Simplify 2(3j-6).
Tap for more steps...
Step 2.1
Apply the distributive property.
15j+6=2(3j)+2-6
Step 2.2
Multiply.
Tap for more steps...
Step 2.2.1
Multiply 3 by 2.
15j+6=6j+2-6
Step 2.2.2
Multiply 2 by -6.
15j+6=6j-12
15j+6=6j-12
15j+6=6j-12
Step 3
Move all terms containing j to the left side of the equation.
Tap for more steps...
Step 3.1
Subtract 6j from both sides of the equation.
15j+6-6j=-12
Step 3.2
Subtract 6j from 15j.
9j+6=-12
9j+6=-12
Step 4
Move all terms not containing j to the right side of the equation.
Tap for more steps...
Step 4.1
Subtract 6 from both sides of the equation.
9j=-12-6
Step 4.2
Subtract 6 from -12.
9j=-18
9j=-18
Step 5
Divide each term in 9j=-18 by 9 and simplify.
Tap for more steps...
Step 5.1
Divide each term in 9j=-18 by 9.
9j9=-189
Step 5.2
Simplify the left side.
Tap for more steps...
Step 5.2.1
Cancel the common factor of 9.
Tap for more steps...
Step 5.2.1.1
Cancel the common factor.
9j9=-189
Step 5.2.1.2
Divide j by 1.
j=-189
j=-189
j=-189
Step 5.3
Simplify the right side.
Tap for more steps...
Step 5.3.1
Divide -18 by 9.
j=-2
j=-2
j=-2
(
(
)
)
|
|
[
[
]
]
7
7
8
8
9
9
4
4
5
5
6
6
/
/
^
^
×
×
>
>
1
1
2
2
3
3
-
-
+
+
÷
÷
<
<
π
π
,
,
0
0
.
.
%
%
=
=
 [x2  12  π  xdx ]